Supplementation of Perkinsus marinus Cultures with Host Plasma or Tissue Homogenate Enhances Their Infectivity - Earnhart, Christopher G. (American Society for Microbiology, 2004)
The protozoan oyster parasite Perkinsus marinus can be cultured in vitro in a variety of media; however, this has been associated with a rapid attenuation of infectivity. Supplementation of defined media with products of P. marinus-susceptible (Crassostrea virginica) and -tolerant (Crassostrea gigas, Crassostrea ariakensis) oysters alters proliferation and protease expression profiles and induces differentiation into morphological forms typically seen in vivo. It was not known if attenuation could be reversed by host extract supplementation. To investigate correlations among these changes as well as their association with infectivity, the effects of medium supplementation with tissue homogenates from both susceptible and tolerant oyster species were examined. The supplements markedly altered both cell size and proliferation, regardless of species; however, upregulation of low-molecular-weight protease expression was most prominent with susceptible oysters extracts. Increased infectivity occurred with the use of oyster product-supplemented media, but it was not consistently associated with changes in cell size, cell morphology, or protease secretion and was not related to the susceptibility of the oyster species used as the supplement source.